Influence of work stressors on job burnout among 4- and 5-star hotel kitchen staff in the Klang Valley, Malaysia - Abdul Hadi, Arnieyantie (2023)
Hotel kitchen staff is a pillar for the operation and provision of quality service for a hotel. However, hotel kitchen staff are frequently exposed to negative physical and psychological demands that lead to job burnout and intention to leave, which can seriously impact the hotel industry. It was reported earlier that four- and five-star hotels in Klang Valley experienced a high turnover rate. Several stressors of job burnout related to work environment aspects and job characteristics were recently studied. Hence, the main objective of this study is to investigate the work stressors as a key factor influencing job burnout among the hotel kitchen staff. Further investigation was performed to explain all significant factors contributing to job burnout. A mixedmethod explanatory sequential design approach was applied for this study. A total of 329 survey questionnaires were collected among kitchen staff in four- and five-star hotels in Klang Valley area to measure the relationship between predictors and job burnout. Based on survey findings, interview questions were developed, and six participants selected from the quantitative phase were interviewed to further elaborate on the role of predictors in affecting job burnout. Data analysis for quantitative data was analysed using SmartPLS software (version 3), while qualitative data using ATLAS.ti (version 7). The survey findings show that work stressors such as intradepartmental teamwork, job autonomy, role conflict, supervisor support, and work overload (p<0.05) significantly predict job burnout among the hotel kitchen staff in four- and five-star hotels in Klang Valley. Factors such as intradepartmental communication, physical work environment, and supervisor support significantly influenced job dissatisfaction. Each factor has acceptable internal reliability (Cronbach α = 0.789-0.941) and confirmatory factor analysis result provided evidence for convergent overall factor loading>0.7, AVE>0.5, CR>0.7) and discriminant validity (HTMT ratio <0.90). The result of structural equation modelling showed the proposed model to be predictive of job burnout (R2 = 0.428, Q2 = 0.164) and job dissatisfaction (R2 = 0.405, Q2 = 0.278). The result also demonstrated job dissatisfaction as a mediator between physical work environment and job burnout. Qualitative findings further explain that intradepartmental poor teamwork causes unstandardized products, communication breakdown, and work overload. Trust with SOP as limitations is a type of job autonomy given to kitchen staff. Meanwhile, inconsistent, multiple instructions and multitasking expectations from top management cause role conflict. Emotional and physical support from supervisor in daily tasks can lessen job burnout. Shortage of staff, lack of cooperation within the department, compulsory overtime, and last-minute events causing work overload. Delegating a task according to the job position, schedule, and advance preparation can lower stress. Effective leadership and individual achievement support given by supervisors increased job satisfaction. Loud noise in the kitchen, wrong instruction, improper language, and indirect instruction are intradepartmental communication issues influencing job dissatisfaction. The kitchen staff also expects to work with complete equipment and proper layout to satisfy the physical work environment. Inconclusion, the results can guide managers develop strategies to combat job burnout among hotel kitchen staff by targeting on significant work stressors. The information gained may also guide managers and executive chefs to improve their physical work environments and strengthen interaction within the kitchen department.